2021
DOI: 10.1111/jon.12959
|View full text |Cite
|
Sign up to set email alerts
|

MR diffusion and dynamic‐contrast enhanced imaging to distinguish meningioma, paraganglioma, and schwannoma in the cerebellopontine angle and jugular foramen

Abstract: Background and Purpose: Differentiation of meningiomas, paragangliomas, and schwannomas in the cerebellopontine angle and jugular foramen remains challenging when conventional MRI findings are inconclusive. This study aimed to assess the clinical utility of diffusion-weighted imaging (DWI) and dynamic contrast-enhanced MRI (DCE-MRI) findings for tumor type differentiation and to identify the most significant diagnostic parameters. Methods: This retrospective study included 57 patients with pathologically confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, this technique has not been often utilized for intracranial extra‐axial tumors 13,14 . Paragangliomas are hypervascular tumors with prominent vascular structures, and prior studies using dynamic contrast‐enhanced perfusion MRI (DCE‐MRI) showed that fractional plasma volume, which represents tumor's microvascularity, was higher in paragangliomas than in schwannomas 12,18 . Our result suggests that CBV and CBF can also be promising parameters to differentiate paragangliomas and schwannomas.…”
Section: Discussionmentioning
confidence: 72%
“…However, this technique has not been often utilized for intracranial extra‐axial tumors 13,14 . Paragangliomas are hypervascular tumors with prominent vascular structures, and prior studies using dynamic contrast‐enhanced perfusion MRI (DCE‐MRI) showed that fractional plasma volume, which represents tumor's microvascularity, was higher in paragangliomas than in schwannomas 12,18 . Our result suggests that CBV and CBF can also be promising parameters to differentiate paragangliomas and schwannomas.…”
Section: Discussionmentioning
confidence: 72%
“…Breger et al [29] studied the signal intensity value on contrast-enhanced T1-weighted image of benign extra-axial tumors on the brain, the results also show that the signal values on T1W after injection of schwannomas is higher than meningiomas. Research by Ota et al [30] reported that differentiation between meningiomas and schwannomas in the cerebellopontine angle and jugular foramen can be relied on some parameters on dynamic-contrast enhanced imaging (DCE-MRI), with significant differences between these two tumor types for the fractional blood plasma volume (Vp) and extracellular extravascular space (Ktrans) (p < 0.001, <0.001, respectively; and AUC of Vp values > 0.9). The report by Meng et al [31] assessed spinal tumor vascularity on DCE-MRI and showed that it is an accurate technique.…”
Section: Discussionmentioning
confidence: 99%
“…Ota, Y. et al detected that the apparent diffusion coefficient (ADC) and the diffusion-weighted imaging (DWI) were important and useful to differentiate SDH mutation [ 28 , 29 ]. Ktrans as a diagnostic parameter of dynamic contrast-enhanced MRI (DCE-MRI) for PGs [ 30 ] could predict the potential efficacy of radiotherapy for paragangliomas [ 31 ]. Although radiotherapy for JFPs is widely described in the literature, efficacy ought to be verified for a longer period of time [ 18 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%